Implementation Of Halal Value Chain In Business In Islamic Boarding Schools - Dzikrulloh, Dzikrulloh; Koib, Ahmad (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2020)
This study aims to determine the implementation of the halal value chain in the Islamic Boarding School business. In this article, the focus of the study is on the oyster mushroom business, starting from the process of cultivating oyster mushrooms to being processed food, and the sales process at the Nurul Amanah Islamic Boarding School, Basanah, Bangkalan.This type of study is a qualitative study with observational study methods. While the data collection methods were carried out through observation, interviews, and documentation.The results of the study on the application of the halal value chain at the Nurul Amanah Islamic Boarding School Bangkalan indicate that the input process for making oyster mushroom raw materials, processing oyster mushrooms into mushroom chips, and product marketing processes. The input process for making oyster mushrooms starts from providing a place, making planting media, making baglog and sterilizing processes, making mushroom seeds and sowing seeds, maintenance, and harvesting. Then the management process into mushroom chips starts from the ingredients, the frying process, drying, product packaging and marketing stages. Everything is in accordance with Indonesian Government Regulation No. 31 of 2019 concerning Implementing Regulations of Law No. 33 of 2014 concerning Guaranteed Halal Products and a List of Non-Critical Materials (Halal Positive List of Materials) for its supporting materials. It can be concluded that the Nurul Amanah Islamic Boarding School has implemented a halal value chain.